IPCC default emission factors for boreal drained organic agricultural soils do not capture the enhanced emissions after grass renewal - Hetmanenko, Viktoriia; Lång, Kristiina; Saarnio, Sanna; Kekkonen, Hanna (Finnish Environment Institute, 2025)
Based on the default emission factors, grass cultivation on drained organic soils is a lower source of greenhouse gas emissions than an annual crop cultivation. However, the emission factors may be biased because the published measurement data are limited and often short-term. Most of the publications cited in the "2013 Supplement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories: Wetlands" for grasslands on drained organic soils in the boreal climate exclude measurements from long-term leys and do not provide data on GHG emissions following practices such as ploughing, re-seeding, or chemical treatments. Only a limited number of studies document the occurrence of soil tillage and herbicide application during experiments, and those that do often fail to include varied seasonal combinations of these events. This rapid communication highlights the need for long-term greenhouse gases exchange observations across larger variations of grass renewal techniques to provide further insights into carbon and nitrogen emissions from drained organic soils.
Keywords: emissions; drained organic soils; greenhouse gases; agriculture